Fenomena Looting Pada Generasi Z Dan Pengaruhnya Dengan Civic Disposition - Raisha Saputri Eryanda; Rahmah Azzahra; Najma Zahira Devianti; Muhammad Akbar Fawwaz; Ibrahim Taghyirul Islam Assajidin; Ahmad Fu'adin (International Forum of Researchers and Lecturers, 2023)
This study aims to describe the impact of looting on a person's civic character or Civic disposition in the context of people's lives. Looting refers to the act of appropriating other people's property for personal gain. By combining qualitative data from various sources, including related literature, research reports, and interviews with individuals involved in looting, this study yielded significant findings. The results of the analysis show that looting negatively affects a person's Civic disposition. The act of looting violates the moral and ethical values ​​that underlie active and responsible participation in society. Individuals who are involved in acts of stealing tend to show a lack of sense of responsibility, integrity, and empathy towards victims and the wider community. Looting destroys social ties that are necessary for a harmonious life in society. Overall, this research highlights the importance of awareness of the negative impact of looting on Civic disposition. Education, prevention and rehabilitation are needed to improve behavior and rebuild strong civic character, with the aim of promoting a just and civilized society.